Clinical Experience with the Elema Vario Pacemaker. Issue 5945 (14th December 1974) - Roy, P. R.; Sowton, Edgar
Abstract : Early problems after implantation of an endocardial electrode for permanent pacing occur in many patients. Difficulties can be anticipated in many of these patients and their management made much easier by a knowledge of the daily endocardial threshold obtained in patients with an implanted Elema Verio pacing unit by a simple non-invasive technique using a magnet and electrocardiogram. Twenty patients are described in whom permanent pacing with an Elema Vario unit was undertaken. The practical advantages of this unit can be readily seen in the patient who developes exit block or in the patient with obstructive airways disease, in whom frequent coughing or right ventricular hypertrophy may make stable electrode placement difficult. The chief advantage of the Elema Vario pacemaker is the extreme simplicity with which knowledge of the endocardial threshold can be obtained.